Neuropeptides and Behaviors: How Small Peptides Regulate Nervous System Function and Behavioral Outputs - Bhat, Umer Saleem; Shahi, Navneet; Surendran, Siju; Babu, Kavita (Frontiers in Molecular Neuroscience, 2021)
One of the reasons that most multicellular animals survive and thrive is because of the adaptable and plastic nature of their nervous systems. For an organism to survive, it is essential for the animal to respond and adapt to environmental changes. This is achieved by sensing external cues and translating them into behaviours through changes in synaptic activity. The nervous system plays a crucial role in constantly evaluating environmental cues and allowing for behavioural plasticity in the organism. Multiple neurotransmitters and neuropeptides have been implicated as key players for integrating sensory information to produce the desired output. Because of its simple nervous system and well-established neuronal connectome, C. elegans acts as an excellent model to understand the mechanisms underlying behavioural plasticity. Here, we critically review how neuropeptides modulate a wide range of behaviours by allowing for changes in neuronal and synaptic signalling. This review will have a specific focus on feeding, mating, sleep, addiction, learning and locomotory behaviours in C. elegans. With a view to understand evolutionary relationships, we explore the functions and associated pathophysiologies of C. elegans neuropeptides that are conserved across different phyla. Further, we discuss the mechanisms of neuropeptidergic signalling and how these signals are regulated in different behaviours. Finally, we attempt to provide insight into developing potential therapeutics for neuropeptide-related disorders.